Some biological aspects of the Silurid Catfish, Bagrus docmak (Forksskal, 1775) in Lake Victoria, Kenya. Issue 3 (1st July 2021) - Yongo, Edwine; Agembe, Simon
Abstract: Bagrus docmak is indigenous to Lake Victoria, being an important source of economic livelihoods to communities around the lake. Although its stocks in the lake are facing intense fishing, predation and ecological changes, data on its biological aspects are scanty, being the basis for the current study. Fish samples for the present study were collected using gillnets of 10‐ and 50‐mm mesh sizes. The length and weight of individual fish caught were measured in the field, while stomachs were preserved in 5% formalin and taken to the laboratory for gut content analysis. The overall sex ratio (male: female) was 1.0:1.26, and did not deviate significantly from 1:1. The lengths of the fish ranged from 12.0 to 55.0 cm TL and the weights ranged between 20.0 and 1650.0 g, with a mean length and weight of 32.7 cm TL and 351.2 g, respectively. The fish were in a good condition with mean condition factors (K) of 1.0, 1.01 and 0.97 for all fish, females and males, respectively. The fish exhibited a negative allometric growth pattern, with a length–weight relationship slope ( b ) of 2.90, 2.94 and 2.94 for all fish, females, and males, respectively. Stomach analyses revealed an ontogenetic diet shift, where juveniles of less than 30 cm TL feeding exclusively on Caridina nilotica . With increasing size, the fish ingested insects and other fish species, including barbus, bivalves, haplochromines, crabs and detritus in variable quantities. The results of the present study provide useful information on the biological aspects of B . docmak useful for its management and comprehensive stock assessment when required. It also provides insights into the feeding ecology of this fish in view of the changing Lake Victoria ecosystem. Accurate Knowledge regarding its food requirements can inform feed formulation for its successful culture.